2014
DOI: 10.1111/jora.12157
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Poverty and Chaos in the Development of Task Persistence Among Adolescents

Abstract: Late adolescents (N = 256; M age = 17.5) who spent a larger proportion of their early life in poverty exhibited less persistence when confronted by a challenging task. Greater chaos during early adolescence also predicted less task persistence at age 17. However, the effects of poverty were moderated by chaos such that if chaos levels were high during early adolescence, task persistence was uniformly lower among late adolescents, irrespective of childhood poverty. Only when chaos levels were relatively low did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
(66 reference statements)
1
11
0
Order By: Relevance
“…Such findings corroborate previous studies in which higher household chaos and lower SES were longitudinally associated with lower task persistence, an indicator of self-control among adolescents (Fuller-Rowell et al, 2015). However, the present study extends these findings by demonstrating how higher household chaos and lower SES may identify those who are most vulnerable to exhibit no growth in self-control over time, rather than simple associations with self-control for the whole sample.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Such findings corroborate previous studies in which higher household chaos and lower SES were longitudinally associated with lower task persistence, an indicator of self-control among adolescents (Fuller-Rowell et al, 2015). However, the present study extends these findings by demonstrating how higher household chaos and lower SES may identify those who are most vulnerable to exhibit no growth in self-control over time, rather than simple associations with self-control for the whole sample.…”
Section: Discussionsupporting
confidence: 91%
“…The detrimental effects of household chaos on self-control have been shown in early childhood with research indicating that higher household chaos at age three was associated with lower inhibitory control at age four (Hardaway, Wilson, Shaw, & Dishion, 2012). Similarly, other work has demonstrated that adolescents who spent a larger part of their early life in a more chaotic environment showed lower task persistence than adolescents in less chaotic homes (Fuller-Rowell, Evans, Paul, & Curtis, 2015). A recent longitudinal study has also revealed both poverty and household chaos (i.e., disorganization) measured in early childhood were significantly associated with poor self-regulation in kindergarten (Vernon-Feagans et al, 2016).…”
Section: Introductionmentioning
confidence: 76%
“…23 Research has linked chaotic settings with a range of health and behavioral issues in children and adolescents. 2426 A small number of studies have examined the relationship between household chaos and sleep, and most, though not all, 27 have reported increased levels of chaos associated with increased sleep problems in preschool 2830 and school-age children. 31 Household chaos has also been found to mediate the relationships between SES and poor sleep in women 32 as well as between young children’s emotional/behavioral problems and bedtime resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Poor children have been associated with maladaptive coping strategies and may require support to employ the shift‐and‐persist strategy. Supportive role models have been shown to diminish the effects of childhood adversity on pathogenic mechanisms that may lead to chronic disease .…”
Section: External Buffersmentioning
confidence: 99%
“…110 Health benefits have been shown in decreased levels of inflammation in asthmatic children, 111 the regulation of inflammation in adolescents and their parents, 108 and the delay of disease progression in adults who have experienced childhood poverty. 112 Poor children have been associated with maladaptive coping strategies 113 and may require support to employ the shift-and-persist strategy. Supportive role models have been shown to diminish the effects of childhood adversity on pathogenic mechanisms that may lead to chronic disease.…”
Section: External Buffersmentioning
confidence: 99%